1975
DOI: 10.1021/j100586a001
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular decomposition rates of cyclobutanone, 3-oxetanone, and perfluorocyclobutanone. RRKM [Rice-Ramsperger-Kassel-Marcus] calculation of internally converted hot molecules

Abstract: Publication costs assisted by the University of CaliforniaSpecific rate constants for the unimolecular decomposition of cyclobutanone (CB), 3-oxetanone (OXTN), and perfluorocyclobutanone (PFCB) have been calculated by the general RRKM computer program of Hase and Bunker. PFCB is calculated to react slower and OXTN faster than CB for a given photoactivation energy, The calculation supports the internal conversion mechanism in the photolysis of PFCB, and it predicts that the observable pressure quenching of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The first primary thermal decomposition channel of 3-oxetanone produces formaldehyde and ketene (Reaction 1), products previously indicated for photolysis. 19 Evidence for the formation of ketene is found in FTIR bands at 2142 ( …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The first primary thermal decomposition channel of 3-oxetanone produces formaldehyde and ketene (Reaction 1), products previously indicated for photolysis. 19 Evidence for the formation of ketene is found in FTIR bands at 2142 ( …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In an earlier work, RRKM theory was used to investigate the ketene dissociation channel of 3-oxetanone. The rate constants were computed using the energy barrier of analogous cyclobutanone molecule as detailed electronic structure data were not available on the dissociation pathways of 3-oxetanone.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Several studies have been reported in the literature on the decomposition reactions of small heterocyclic molecules and their substituted variants. For the thermal decomposition of 3oxetanone, two different dissociation patterns 16,17 can be considered as shown in Figure 1. The first one involves the formation of ketene (CH 2 CO) + formaldehyde (HCHO), and the second one leads to ethylene oxide (oxirane, c-C 2 H 4 O) + carbon monoxide (CO).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations